Lattice groups - Kurdachenko, L.A.; Yashchuk, V.S.; Subbotin, I.Ya. (Algebra and Discrete Mathematics, 2015)
In this paper, we introduce some algebraic struc-ture associated with groups and lattices. This structure is a semi-group and it appeared as the result of our new approach to thefuzzy groups andL-fuzzy groups whereLis a lattice. This approachallows us to employ more convenient language of algebraic structuresinstead of currently accepted language of functions.